Evaluating Biventricular Myocardial Velocity and Interventricular Dyssynchrony in Adult Patients During the First Year After Heart Transplantation. Issue 3 (15th February 2020) - Sarnari, Roberto; Blake, Allison M.; Ruh, Alexander; Abbasi, Muhannad A.; Pathrose, Ashitha; Blaisdell, Julie; Dolan, Ryan S.; Ghafourian, Kambiz; Wilcox, Jane E.; Khan, Sadiya S.; Vorovich, Esther E.; Rich, Jonathan D.; et al.
Abstract : Background: Magnetic resonance tissue phase mapping (TPM) measures three‐directional myocardial velocities of the left and right ventricle (LV, RV). This noninvasive technique may supplement endomyocardial biopsy (EMB) in monitoring grafts post‐heart transplantation (HTx). Purpose: To assess biventricular myocardial velocity alterations in grafts and investigate the relationship between velocities and acute cellular rejection (ACR) episodes. Study Type: Prospective. Subjects: Twenty‐seven patients within 1 year post‐HTx (49 ± 13 years, 19 M) and 18 age‐matched controls (49 ± 15 years, 12 M). Field Strength/Sequence: 1.5T, 2D balanced steady‐state free precession, and TPM. Assessment: Ventricular function: end‐diastolic and end‐systolic volumes, stroke volumes, ejection fraction (EF), and myocardial mass. TPM velocities: peak‐systolic and peak‐diastolic velocities, cardiac twist, and interventricular dyssynchrony. ACR rejection episodes: International Society for Heart and Lung Transplantation grading of EMB specimens. Statistical Tests: The Lilliefors test for normality, unpaired t ‐tests, and Wilcoxon rank‐sum tests for normally and nonnormally distributed data, respectively, were used, as well as multivariate regression for confounding variables and Pearson's correlation for associations between TPM velocities and global function. Results: Compared to controls, HTx patients demonstrated reduced biventricular systolic longitudinal velocities (LV: 5.2 ± 2.1 vs. 4.0 ± 1.5 cm/s, P < 0.05; RV: 4.2 ± 1.3 vs. 3.1 ± 1.2 cm/s, P < 0.01). Correlation analysis revealed significant positive relationships for biventricular EF with radial peak velocities of the same ventricle in both systole and diastole (LV systole: r = 0.48, P < 0.01; LV diastole: r = 0.28, P < 0.05; RV systole: r = 0.35, P < 0.01; RV diastole: r = 0.36, P < 0.01). Segmentally, longitudinal velocities were impaired in 7/16 LV segments and 5/10 RV segments in systole and 7/10 RV segments in diastole. TPM analysis in studies with >4 preceding ACR episodes showed globally reduced RV and LV systolic radial velocity, and segmentally reduced radial and longitudinal systolic velocities. Data Conclusion: Biventricular global and segmental velocities were reduced in HTx patients. Patients with >4 rejection episodes showed reduced myocardial velocities. The TPM sequence may add functional information for monitoring graft dysfunction. Level of Evidence: 2 Technical Efficacy Stage: 2 J. Magn. Reson. Imaging 2020;52:920–929.